Atividade anticonvulsivante do óleo de peixe - Banderó, Cristina Ruedell Reschke (2010)
Methylmalonic acidemias are inherited metabolic disorders characterized by methylmalonate (MMA) accumulation and neurological dysfunction, including seizures. Dietary fatty acids are known as an important energy source and reduce seizure activity in selected acute animal models. This study investigates whether the chronic treatment with fish oil or with oleic acid attenuates MMA-induced seizures. Adult male Wistar rats were treated with fish oil (85 mg/kg), oleic acid (85 mg/kg) or vehicle (0.42 % aqueous Cremophor EL , 4 mL/kg/body weight/day), p.o., for 75 days. In the 73th day were implanted a cannula in the right lateral ventricle with electrodes over the parietal cortex for EEG recording. In the 76th day half the animals from each group were injected with NaCl (2.5 μmol/2.5 μL, i.c.v.), and the other half with MMA (2.5 μmol/2.5 μL, i.c.v.), and seizure activity was measured by EEG recording with concomitant behavior monitoring. The effect of prostaglandin E2 (PGE2) on Na+,K+-ATPase activity of slices of cerebral cortex from NaCl-injected (control) animals was determined. Fish oil administration increased the latency for MMA-induced tonic-clonic seizures and reduced the mean amplitude of ictal EEG recordings. Oleic acid decreased mean amplitude of ictal EEG recordings. Treatment with fish oil prevented PGE2-induced decrease of Na+,K+-ATPase activity in cortical slices in vitro. The results support a major anticonvulsant role for fish oil against MMA-induced seizures. The decreased sensitivity of Na+,K+-ATPase from fish oil-treated animals to the inhibitory effect of PGE2 may be related to its currently reported anticonvulsant activity.